Evaluating police uses of force - Stoughton, Seth W. (New York University Press, 2020)
Introduction -- The Constitutional Law Standard -- The State Law Standard -- The Administrative Standard -- The Community Expectations Standard -- Tactical Considerations -- Force Options: Tools, Techniques, and Weaponry -- Conclusion